Upaya Guru dalam Mengatasi Kesulitan Membaca dan Menulis Siswa Kelas I dan II Sekolah Dasar - Zulfi Idayanti; Muh. Asharif Suleman; Muhammad Najib; Ani Khoirotun Nisa; Alfian Eko Widodo Adi Prasetyo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The ability to read and write plays a crucial role in the learning process. However, not all students have the same reading and writing skills at an early age, especially in grades I and II. The study aims to explore the efforts made by teachers in dealing with students who have difficulty reading at levels I and II. The research methodology used is field studies with data collection through observation. The results showed that teachers used different teaching strategies, including paying more attention to students who still have difficulty reading and writing, guiding students to write letters correctly, and giving extra hours before learning takes place. Furthermore, students were gathered in one place to learn to read and write using teaching materials such as reading books and alphabetic letters. Besides, there are internal and external factors that influence. The internal factors of the family environment are less encouraging students to be trained to learn to read, so the ability to read is still less, while the external factors are the influence of the playing environment, including their friends. Thus, this research is useful as an example of the efforts that educators, especially teachers, can make when faced with similar circumstances, namely, students who still have difficulty reading and writing.